The potential of quarry dust (QDC) as partial sand replacement in concrete - Imran N.F.; Tutur N.; Ramli M.Z.; Zaini M.F.S.M.; Hamzah N. (American Institute of Physics Inc., 2023)
Sand is one of the important part in construction. The mining of sand also causes environmental problems which can affect the habitats and environment. The demand of sand makes the problem become very worst. To overcome this problem, partial replacement of sand can be done to reduce the amount of sand. In many country, quarry dust may become as the alternative choice to replace the sand. Quarry dust is a byproduct from quarrying activities. Recyclable of this source will help to reduce the problem. The objective of the study is to determine the compressive strength of the concrete containing quarry dust as partially sand replacement. This study present the potential of quarry dust as partial replacement in concrete. Quarry dust is used as partial sand replacement for sand namely as QDC5, QDC10, QDC15, QDC20 and QDC25 for 5%, 10%, 15%, 20% and 25% replacement respectively following normal concrete as OPC. All specimens were tested for compressive strength at the age of 7, 14 and 28 days. Based on the result, it shown the compressive strength of concrete increase due to increasing amount of replacement of quarry dust to the sand for all curing time which is 7 days, 14 days and 28 days. 2018 Author(s).